Cobalt-based oxide catalyst material and preparation method and application thereof

By doping manganese and supported iridium in the cobalt oxide catalyst, cobalt-based oxide catalyst materials were prepared, which solved the problem of poor catalyst activity and stability in acidic media, and achieved an efficient and low-cost acidic water decomposition electrolytic cell system.

CN119571388AInactive Publication Date: 2025-03-07ELECTRIC POWER RESEARCH INSTITUTE OF STATE GRID SHANDONG ELECTRIC POWER COMPANY +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411652274.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the oxygen evolution reaction catalyst used for hydrogen production by water electrolysis of proton exchange membranes exhibits poor activity and stability in acidic media, and the high cost and scarcity of precious metal catalysts limit their large-scale application.

Method used

Cobalt-based oxide catalyst material is prepared by doping manganese into the cobalt oxide catalyst and supporting iridium, and its catalytic activity and stability under acidic conditions are optimized.

Benefits of technology

It significantly improves the catalytic activity and stability of cobalt-based oxide catalyst materials, is suitable for efficient acid water decomposition electrolytic cell systems, and reduces the cost and scarcity of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571388A_ABST
    Figure CN119571388A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of catalyst materials, and discloses a cobalt-based oxide catalyst material and a preparation method and application thereof, and the cobalt-based oxide catalyst material comprises the following raw materials by mass: 0.66-4.66% of carbon cloth; 24.82 to 34.82 percent of cobalt salt; the content of the methylimidazole is 62.32 to 73.32 percent; 0.01 to 0.1 percent of manganate; and 0.01 to 0.1 percent of iridium salt. The cobalt-based oxide catalyst material is prepared by doping manganese and loading iridium in the cobalt oxide catalyst, the catalytic activity and the stability of the cobalt oxide in an oxygen evolution reaction under an acidic condition are optimized, and compared with other cobalt-based oxide catalysts, the cobalt-based oxide catalyst has the advantages that the performance is remarkably improved, and the cobalt-based oxide catalyst material is suitable for an efficient acidic water decomposition electrolytic bath system; meanwhile, a carbon cloth loaded manganese-doped cobalt oxide material is prepared by doping second metal manganese, so that the structural stability of the cobalt-based oxide catalyst material is improved, the structural collapse caused by dissolution of the catalyst in an acid medium is effectively prevented, and the loss of active ingredients in the catalyst in the reaction process is inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalyst materials, and in particular to a cobalt-based oxide catalyst material and a preparation method and application thereof. Background Art

[0002] As a secondary energy source with zero carbon emissions, hydrogen energy can be deeply coupled with new energy sources, and can achieve large-scale storage of electricity over a long period across seasons through electricity-hydrogen conversion. It can also be used as an energy medium to promote the interconnection, complementarity and coordinated optimization of various energy networks such as electricity, heating, and fuel, thereby improving terminal energy utilization efficiency. Water electrolysis hydrogen production technology is mainly divided into alkaline water electrolysis, proton exchange membrane (PEM) water electrolysis, solid polymer anion exchange membrane water electrolysis, and solid oxide water electrolysis technology. Proton exchange membrane water electrolysis has the advantages of high hydrogen production purity, wide load range, high operating current density, and fast dynamic response speed. It has a good match with the random and volatile power generation mode of new energy generators, and can achieve zero carbon emissions throughout the entire chain. It is currently the most promising green hydrogen preparation technology.

[0003] The oxygen evolution reaction occurring at the anode of a proton exchange membrane electrolyzer involves a four-electron transfer process with slow kinetics, which is the main source of energy consumption for proton exchange membrane water electrolysis. In addition, the high potential (potential is nearly 2V) and strongly acidic working environment (pH value is 1-3) in the proton exchange membrane electrolyzer place extremely high demands on the stability of the catalyst. In recent years, significant progress has been made in electrocatalysts for acidic hydrogen evolution reactions, but the development of high-performance, low-cost electrocatalysts for oxygen evolution reactions remains challenging. This is mainly because most oxygen evolution reaction catalysts exhibit poor activity in acidic media and require higher overpotentials to achieve catalytic current densities comparable to those in alkaline media. In addition, stability issues are also a problem that plagues acidic oxygen evolution reaction catalysts, and even precious metal catalysts (such as ruthenium oxide RuO 2 and iridium oxide IrO 2 ) will also dissolve and degrade in the acidic oxygen evolution reaction. At present, iridium oxide is regarded as one of the most suitable anode catalyst materials for proton exchange membrane water electrolysis technology due to its high catalytic activity and stability. However, the precious metal iridium catalyst is expensive and scarce, which greatly limits their large-scale application.

[0004] Transition metal oxides have great potential in oxygen evolution reaction due to their unique structure and good electrical properties. 3 O 4) is one of the earliest oxygen evolution reaction catalysts studied and adopted in alkaline media due to its unique spinel structure and different oxidation states. Since cobalt-based materials still face problems such as poor conductivity, insufficient active sites and easy structural collapse during the reaction in catalytic oxygen evolution reaction in acidic media, its activity and stability as an oxygen evolution reaction catalyst in proton exchange membrane water electrolysis hydrogen production are much worse than those of precious metal catalysts ruthenium oxide and iridium oxide.

[0005] Therefore, how to provide a cobalt-based oxide catalyst material and its preparation method and application is a problem that needs to be solved urgently. Summary of the invention

[0006] The embodiments of the present invention provide a cobalt-based oxide catalyst material and a preparation method and application thereof to solve the technical problems existing in the prior art.

[0007] In order to have a basic understanding of some aspects of the disclosed embodiments, a brief summary is given below. This summary is not intended to be a general review, nor is it intended to identify key / important components or to delineate the scope of protection of these embodiments. Its only purpose is to present some concepts in a simple form as a preface to the detailed description that follows.

[0008] According to a first aspect of an embodiment of the present invention, a cobalt-based oxide catalyst material is provided.

[0009] In one embodiment, a cobalt-based oxide catalyst material comprises the following raw materials in percentage by weight:

[0010] Carbon cloth 0.66-4.66%;

[0011] Cobalt salt 24.82-34.82%;

[0012] Methylimidazole 62.32-73.32%;

[0013] Manganate 0.01-0.1%;

[0014] Iridium salt 0.01-0.1%.

[0015] In one embodiment, the cobalt salt is cobalt nitrate hexahydrate, and the methylimidazole is 2-methylimidazole.

[0016] In one embodiment, the manganate salt is potassium permanganate, and the iridium salt is iridium trichloride hydrate.

[0017] According to a second aspect of an embodiment of the present invention, a method for preparing a cobalt-based oxide catalyst material is provided.

[0018] In one embodiment, the method for preparing the cobalt-based oxide catalyst material comprises:

[0019] Cutting the carbon cloth into a preset size, performing surface treatment on the carbon cloth by ultrasonic cleaning, and soaking the surface treated carbon cloth in deionized water;

[0020] Weighing a cobalt salt and methylimidazole to prepare a mixed solution, immersing the carbon cloth in the mixed solution, and performing a reaction, washing, and drying process to obtain dimethylimidazole cobalt supported on the carbon cloth;

[0021] The carbon cloth-supported dimethylimidazole cobalt is immersed in a manganate solution to obtain manganese-doped dimethylimidazole cobalt supported on the carbon cloth, and the washed and dried manganese-doped dimethylimidazole cobalt supported on the carbon cloth is immersed in an iridium salt solution to obtain manganese-iridium-doped dimethylimidazole cobalt supported on the carbon cloth;

[0022] The manganese iridium doped dimethyl imidazole cobalt supported on carbon cloth is placed in an air atmosphere environment and heated to prepare a carbon cloth supported cobalt-based oxide catalyst material.

[0023] In one embodiment, the surface treatment of the carbon cloth by ultrasonic cleaning includes:

[0024] Soak the carbon cloth in an acetone cleaning tank and ultrasonically clean it for 30 minutes;

[0025] Soak the carbon cloth in an ethanol cleaning tank and ultrasonically clean it for 30 minutes;

[0026] Soak the carbon cloth in a clean water tank and wash for 30 minutes;

[0027] Soak the carbon cloth in a concentrated nitric acid cleaning tank and ultrasonically clean it for 4 hours;

[0028] Soak the carbon cloth in a clean water tank and wash it until the pH value on the surface of the carbon cloth is neutral.

[0029] In one embodiment, the method of weighing a cobalt salt and methylimidazole to prepare a mixed solution, immersing the carbon cloth in the mixed solution, and performing a reaction, washing, and drying process to obtain dimethylimidazole cobalt supported on the carbon cloth comprises:

[0030] Weigh cobalt salt and dissolve it in deionized water, stir evenly to obtain cobalt nitrate solution;

[0031] Weigh methylimidazole and dissolve it in deionized water, stir evenly to obtain a methylimidazole solution;

[0032] adding the methylimidazole solution to the cobalt nitrate solution to obtain a mixed solution;

[0033] The carbon cloth was immersed in the mixed solution, reacted at room temperature for 4 hours, repeatedly washed with deionized water, and dried in an oven to obtain dimethylimidazole cobalt supported on the carbon cloth.

[0034] In one embodiment, the cobalt salt is cobalt nitrate hexahydrate, and the methylimidazole is 2-methylimidazole.

[0035] In one embodiment, the temperature of the oven is 60°C.

[0036] In one embodiment, immersing the carbon cloth-supported dimethyl imidazole cobalt in a manganate solution to obtain the carbon cloth-supported manganese-doped dimethyl imidazole cobalt, and immersing the cleaned and dried carbon cloth-supported manganese-doped dimethyl imidazole cobalt in an iridium salt solution to obtain the carbon cloth-supported manganese-iridium-doped dimethyl imidazole cobalt comprises:

[0037] Weigh permanganate and dissolve it in deionized water, stir evenly to obtain a manganate solution;

[0038] The carbon cloth-supported dimethyl imidazolium cobalt is immersed in a manganate solution, and then ice-bathed, washed and dried to obtain the carbon cloth-supported manganese-doped dimethyl imidazolium cobalt;

[0039] Weigh iridium salt and dissolve it in deionized water, stir evenly to obtain an iridium salt solution;

[0040] The manganese-doped dimethylimidazole cobalt supported on the carbon cloth is immersed in an iridium salt solution, and the manganese-iridium-doped dimethylimidazole cobalt supported on the carbon cloth is obtained through immersion, washing and drying.

[0041] In one embodiment, the step of immersing the carbon cloth-supported cobalt dimethyl imidazole in a manganate solution, performing an ice bath, washing, and drying to obtain the carbon cloth-supported manganese-doped cobalt dimethyl imidazole comprises:

[0042] The dimethylimidazole cobalt supported on the carbon cloth was placed in an ice bath in a potassium permanganate solution for 30 minutes, and the dimethylimidazole cobalt supported on the carbon cloth was taken out and repeatedly washed with deionized water and ethanol;

[0043] The washed carbon cloth-supported dimethyl imidazole cobalt is placed in a vacuum drying oven, and after vacuum drying, manganese-doped dimethyl imidazole cobalt supported on the carbon cloth is obtained.

[0044] In one embodiment, the temperature of the vacuum drying oven is 100°C.

[0045] In one embodiment, the step of immersing the carbon cloth-supported manganese-doped cobalt dimethyl imidazole into an iridium salt solution, and obtaining the carbon cloth-supported manganese-iridium-doped cobalt dimethyl imidazole by immersing, washing and drying comprises:

[0046] The manganese-doped dimethyl imidazolium cobalt supported on the carbon cloth was immersed in an iridium trichloride hydrate solution for 24 hours, and the manganese-doped dimethyl imidazolium cobalt supported on the carbon cloth was taken out and rinsed with deionized water;

[0047] The washed carbon cloth-loaded manganese-doped dimethyl imidazole cobalt is placed in a constant temperature box and dried at a constant temperature to obtain the carbon cloth-loaded manganese-iridium-doped dimethyl imidazole cobalt.

[0048] In one embodiment, the temperature of the thermostat is 60°C.

[0049] In one embodiment, the step of placing the carbon cloth-supported manganese-iridium-doped dimethyl imidazole cobalt in an air atmosphere and heating the carbon cloth-supported cobalt-based oxide catalyst material comprises:

[0050] The carbon cloth-supported manganese iridium-doped dimethyl imidazole cobalt was heated to 300° C. at a heating rate of 2° C. / min in an air atmosphere and kept heated for 4 hours to obtain a carbon cloth-supported cobalt-based oxide catalyst material.

[0051] In one embodiment, the manganate salt is potassium permanganate, and the iridium salt is iridium trichloride hydrate.

[0052] According to a third aspect of the embodiments of the present invention, there is provided an application of a cobalt-based oxide catalyst material.

[0053] In some embodiments, the cobalt-based oxide catalyst material is used for electrolysis of water.

[0054] The technical solution provided by the embodiment of the present invention may have the following beneficial effects:

[0055] (1) The present invention prepares a cobalt-based oxide catalyst material by doping manganese into a cobalt oxide catalyst and loading iridium, thereby optimizing the catalytic activity and stability of the oxygen evolution reaction of cobalt oxide under acidic conditions. Compared with other cobalt-based oxide catalysts, the material has significantly improved performance and is suitable for an efficient acidic water splitting electrolyzer system.

[0056] (2) The present invention prepares a carbon cloth-supported manganese-doped cobalt oxide material by doping a second metal manganese, thereby improving the structural stability of the cobalt-based oxide catalyst material, effectively preventing the structural collapse of the catalyst due to dissolution in an acidic medium, inhibiting the loss of active ingredients in the catalyst during the reaction, and improving the stability of the catalyst.

[0057] (3) The present invention increases the number of active sites of the catalyst by loading the precious metal iridium on the cobalt-based oxide catalyst, thereby improving the activity of the catalyst.

[0058] (4) The present invention improves the conductivity of the cobalt-based oxide catalyst material by carbon cloth loading, thereby improving the kinetic activity and stability of the entire catalyst.

[0059] It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0061] Figure 1 is a flow chart showing a method for preparing a cobalt-based oxide catalyst material according to an exemplary embodiment;

[0062] Figure 2 is a comparative example 2 (Co 3 O 4 / CC), Comparative Example 3 (IrCoO / CC), Comparative Example 4 (CoMnO / CC), and Example 1 (IrCoMnO / CC);

[0063] Figure 3 is a comparative example 2 (Co 3 O 4 / CC), Comparative Example 3 (IrCoO / CC), Comparative Example 4 (CoMnO / CC), and Raman comparison of Example 1 (IrCoMnO / CC);

[0064] Figure 4 is a comparative example 2 (Co 3 O 4 / CC), comparative example 3 (IrCoO / CC), comparative example 4 (CoMnO / CC), scanning electron microscope images of Example 1 (IrCoMnO / CC);

[0065] Figure 5 is a high-resolution projection electron microscope image of the morphology and structure of Example 1 (IrCoMnO / CC) according to an exemplary embodiment;

[0066] Figure 6 is a comparative example 2 (Co 3 O 4 / CC), Comparative Example 3 (IrCoO / CC), Comparative Example 4 (CoMnO / CC), and Example 1 (IrCoMnO / CC) tested the linear sweep voltammetry curves of the acidic oxygen evolution reaction;

[0067] Figure 7 is a comparative example 2 (Co 3 O 4 / CC), Comparative Example 3 (IrCoO / CC), Comparative Example 4 (CoMnO / CC), and Example 1 (IrCoMnO / CC) test the Tafel slope diagram of the acidic oxygen evolution reaction. DETAILED DESCRIPTION

[0068] The following description and the accompanying drawings fully illustrate the specific embodiments of this paper so that those skilled in the art can practice them. The parts and features of some embodiments may be included in or replace the parts and features of other embodiments. The scope of the embodiments herein includes the entire scope of the claims, and all available equivalents of the claims.

[0069] An embodiment of a cobalt-based oxide catalyst material of the present invention.

[0070] In this optional embodiment, the cobalt-based oxide catalyst material includes the following raw materials in percentage by mass:

[0071] Carbon cloth 0.66-4.66%; cobalt salt 24.82-34.82%; methylimidazole 62.32-73.32%; manganate 0.01-0.1%; iridium salt 0.01-0.1%.

[0072] In this optional embodiment, the cobalt-based oxide catalyst material includes: 4.66 g of carbon cloth; 30.82 g of cobalt salt; 64.32 g of methylimidazole; 0.1 g of manganate; and 0.1 g of iridium salt.

[0073] In this optional embodiment, the cobalt-based oxide catalyst material includes: 0.66 g of carbon cloth; 26 g of cobalt salt; 73.32 g of methylimidazole; 0.01 g of manganate; and 0.01 g of iridium salt.

[0074] In this optional embodiment, the cobalt-based oxide catalyst material includes: 2.66 g of carbon cloth; 29.82 g of cobalt salt; 68.32 g of methylimidazole; 0.1 g of manganate; and 0.1 g of iridium salt.

[0075] In this optional embodiment, the cobalt salt is cobalt nitrate hexahydrate, and the methylimidazole is 2-methylimidazole.

[0076] In this optional embodiment, the manganate is potassium permanganate, and the iridium salt is iridium trichloride hydrate.

[0077] Figure 1 An embodiment of a method for preparing a cobalt-based oxide catalyst material of the present invention is shown.

[0078] In this optional embodiment, the method for preparing the cobalt-based oxide catalyst material comprises:

[0079] Step S101, cutting a carbon cloth of a preset size, performing surface treatment on the carbon cloth by ultrasonic cleaning, and soaking the surface treated carbon cloth in deionized water;

[0080] Step S103, weighing cobalt salt and methylimidazole to prepare a mixed solution, immersing the carbon cloth in the mixed solution, and performing reaction, washing and drying to obtain dimethylimidazole cobalt supported on the carbon cloth;

[0081] Step S105, immersing the carbon cloth-supported dimethylimidazole cobalt in a manganate solution to obtain manganese-doped dimethylimidazole cobalt supported on the carbon cloth, and immersing the washed and dried manganese-doped dimethylimidazole cobalt supported on the carbon cloth in an iridium salt solution to obtain manganese-iridium-doped dimethylimidazole cobalt supported on the carbon cloth;

[0082] Step S107 , placing the carbon cloth-supported manganese-iridium-doped dimethyl imidazole cobalt in an air atmosphere, and heating the environment to prepare a carbon cloth-supported cobalt-based oxide catalyst material.

[0083] In this optional embodiment, the surface treatment of the carbon cloth by ultrasonic cleaning includes:

[0084] Soak the carbon cloth in an acetone cleaning tank and ultrasonically clean it for 30 minutes;

[0085] Soak the carbon cloth in an ethanol cleaning tank and ultrasonically clean it for 30 minutes;

[0086] Soak the carbon cloth in a clean water tank and wash for 30 minutes;

[0087] Soak the carbon cloth in a concentrated nitric acid cleaning tank and ultrasonically clean it for 4 hours;

[0088] Soak the carbon cloth in a clean water tank and wash it until the pH value on the surface of the carbon cloth is neutral.

[0089] In this optional embodiment, when the cobalt salt and methylimidazole are weighed to prepare a mixed solution, the carbon cloth is immersed in the mixed solution, and dimethylimidazole cobalt supported on the carbon cloth is obtained after reaction, washing and drying. The cobalt salt can be weighed and dissolved in deionized water, and stirred evenly to obtain a cobalt nitrate solution; methylimidazole is weighed and dissolved in deionized water, and stirred evenly to obtain a methylimidazole solution; the methylimidazole solution is added to the cobalt nitrate solution to obtain a mixed solution; the carbon cloth is immersed in the mixed solution, reacted at room temperature for 4 hours, repeatedly washed with deionized water, and dried in an oven to obtain dimethylimidazole cobalt supported on the carbon cloth.

[0090] In this optional embodiment, the cobalt salt is cobalt nitrate hexahydrate, and the methylimidazole is 2-methylimidazole.

[0091] In this optional embodiment, the temperature of the oven is 60°C.

[0092] In this optional embodiment, when immersing the carbon cloth-supported dimethylimidazole cobalt in a manganate solution to obtain the carbon cloth-supported manganese-doped dimethylimidazole cobalt, and immersing the washed and dried carbon cloth-supported manganese-doped dimethylimidazole cobalt in an iridium salt solution to obtain the carbon cloth-supported manganese-iridium-doped dimethylimidazole cobalt, permanganate is weighed and dissolved in deionized water, and stirred evenly to obtain a manganate solution; the carbon cloth-supported dimethylimidazole cobalt is immersed in the manganate solution, and obtained the carbon cloth-supported manganese-doped dimethylimidazole cobalt by ice bath, washing and drying; the iridium salt is weighed and dissolved in deionized water, and stirred evenly to obtain an iridium salt solution; the carbon cloth-supported manganese-doped dimethylimidazole cobalt is immersed in the iridium salt solution, and obtained the carbon cloth-supported manganese-iridium-doped dimethylimidazole cobalt by immersion, washing and drying.

[0093] In this optional embodiment, when immersing the carbon cloth-supported dimethylimidazole cobalt in a manganate solution, performing an ice bath, washing and drying to obtain the carbon cloth-supported manganese-doped dimethylimidazole cobalt, the carbon cloth-supported dimethylimidazole cobalt can be placed in an ice bath in a potassium permanganate solution for 30 minutes, the carbon cloth-supported dimethylimidazole cobalt is taken out, and repeatedly washed with deionized water and ethanol; the washed carbon cloth-supported dimethylimidazole cobalt is placed in a vacuum drying oven, and after vacuum drying, the carbon cloth-supported manganese-doped dimethylimidazole cobalt is obtained.

[0094] In this optional embodiment, the temperature of the vacuum drying oven is 100°C.

[0095] In this optional embodiment, when the manganese-doped dimethylimidazole cobalt supported on carbon cloth is immersed in an iridium salt solution, and the manganese-iridium-doped dimethylimidazole cobalt supported on carbon cloth is obtained by immersion, washing and drying, the manganese-doped dimethylimidazole cobalt supported on carbon cloth can be immersed in an iridium trichloride hydrate solution for 24 hours, the manganese-doped dimethylimidazole cobalt supported on carbon cloth is taken out, and rinsed with deionized water; the rinsed manganese-doped dimethylimidazole cobalt supported on carbon cloth is placed in a constant temperature box, and dried at a constant temperature to obtain the manganese-iridium-doped dimethylimidazole cobalt supported on carbon cloth.

[0096] In this optional embodiment, the temperature of the constant temperature box is 60°C.

[0097] In this optional embodiment, when the manganese iridium doped dimethyl imidazole cobalt supported on carbon cloth is placed in an air atmosphere environment and heated to prepare a carbon cloth-supported cobalt-based oxide catalyst material, the temperature of the manganese iridium doped dimethyl imidazole cobalt supported on carbon cloth can be raised to 300°C at a heating rate of 2°C / min in an air atmosphere and the heating is maintained for 4 hours to obtain a carbon cloth-supported cobalt-based oxide catalyst material.

[0098] In this optional embodiment, the manganate is potassium permanganate, and the iridium salt is iridium trichloride hydrate.

[0099] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0100] Example 1

[0101] 1. Carbon cloth pretreatment

[0102] The carbon cloth was cut into 2 cm×2 cm, and surface treated by ultrasonic washing with acetone for 30 min, ultrasonic washing with ethanol for 30 min, washing with water for 30 min, ultrasonic washing with concentrated nitric acid for 4 h, and washing with water until neutral, and then immersed in deionized water for use.

[0103] 2. Preparation of Cobalt-based Oxide Catalyst Materials Supported by Carbon Cloth

[0104] (1) Dissolve 50 mmol of cobalt nitrate hexahydrate in 40 mL of deionized water and stir evenly;

[0105] (2) Dissolve 0.4 mol of 2-methylimidazole in a beaker containing 40 mL of deionized water, stir for 2 min, and then quickly add the 2-methylimidazole solution to the cobalt nitrate solution;

[0106] (3) Immersing the pre-treated clean carbon cloth in the mixed solution of (2), reacting at room temperature for 4 hours, repeatedly washing with deionized water, and drying in an oven at 60° C. to obtain dimethylimidazole cobalt supported on the carbon cloth.

[0107] (4) Weigh 0.002 g potassium permanganate, dissolve it in 8 ml deionized water, and stir evenly;

[0108] (5) immersing the carbon cloth-supported dimethylimidazole cobalt in a potassium permanganate solution, placing it in an ice bath for 30 minutes, taking out the sample, washing it with deionized water and ethanol several times, and vacuum drying it at 100° C. for 12 hours to obtain the carbon cloth-supported manganese-doped dimethylimidazole cobalt;

[0109] (6) Weigh 2 mmol of iridium trichloride hydrate, dissolve it in 5 mL of deionized water, and stir evenly;

[0110] (7) Immerse the sample in (5) into the solution in (6), take it out after immersion for 24 hours, rinse it with deionized water, and dry it at 60°C;

[0111] (8) The sample in (7) was heated to 300°C at a heating rate of 2°C / min under air atmosphere and kept heated for 4 h to obtain a carbon cloth-supported cobalt-based oxide catalyst material (IrCoMnO / CC).

[0112] Comparative Example 1 (Cobalt dimethylimidazole supported on carbon cloth)

[0113] 1. Carbon cloth pretreatment

[0114] The carbon cloth was cut into 2 cm×2 cm, and surface treated by ultrasonic washing with acetone for 30 min, ultrasonic washing with ethanol for 30 min, washing with water for 30 min, ultrasonic washing with concentrated nitric acid for 4 h, and washing with water until neutral, and then immersed in deionized water for use.

[0115] 2. Preparation of Cobalt Dimethylimidazole Supported on Carbon Cloth

[0116] (1) Dissolve 50 mmol of cobalt nitrate hexahydrate in 40 mL of deionized water and stir evenly;

[0117] (2) Dissolve 0.4 mol of 2-methylimidazole in 40 mL of deionized water, stir for 2 min, and then quickly add the 2-methylimidazole solution to the cobalt nitrate solution;

[0118] (3) Immersing the pre-treated clean carbon cloth in the mixed solution of (2), reacting at room temperature for 4 hours, repeatedly washing with deionized water, and drying in an oven at 60° C. to obtain dimethylimidazole cobalt supported on the carbon cloth.

[0119] Comparative Example 2 (Cobalt oxide supported on carbon cloth - Co 3 O 4 / CC)

[0120] The dimethyl imidazole cobalt prepared in Comparative Example 1 was heated to 300° C. at a heating rate of 2° C. / min in an air atmosphere and kept heated for 4 h to obtain carbon cloth-supported cobalt oxide (Co 3 O 4 / CC).

[0121] Comparative Example 3 (Iridium-modified cobalt-based oxide supported on carbon cloth - IrCoO / CC)

[0122] (1) Weigh 2 mmol of iridium trichloride hydrate and dissolve it in 5 mL of deionized water;

[0123] (2) The dried carbon cloth-supported dimethyl imidazolium cobalt was placed in the above solution, immersed for 24 hours, taken out, rinsed with deionized water, and dried at a constant temperature of 60° C. to obtain carbon cloth-supported iridium-modified dimethyl imidazolium cobalt.

[0124] (3) The iridium-modified dimethylimidazole cobalt supported on carbon cloth is heated to 300° C. at a heating rate of 2° C. / min in an air atmosphere, and the heating is maintained for 4 hours to obtain iridium-modified cobalt-based oxide supported on carbon cloth (IrCoO / CC).

[0125] Comparative Example 4 (Carbon cloth supported manganese doped cobalt-based oxide - CoMnO / CC)

[0126] (1) Weigh 0.002 g potassium permanganate and dissolve it in 8 ml deionized water, stirring evenly;

[0127] (2) immersing the dried carbon cloth-supported dimethyl imidazole cobalt in a potassium permanganate solution, placing it in an ice bath for 30 minutes, taking out the sample, washing it with deionized water and ethanol several times, and vacuum drying it at 100° C. for 12 hours to obtain carbon cloth-supported manganese-doped dimethyl imidazole cobalt;

[0128] (3) The manganese-doped dimethylimidazole cobalt supported on carbon cloth was heated to 300° C. at a heating rate of 2° C. / min in an air atmosphere and kept heated for 4 h to obtain a manganese-doped cobalt-based oxide supported on carbon cloth (CoMnO / CC).

[0129] Results Analysis

[0130] Comparative Example 1 is a precursor prepared in all comparative examples and embodiments.

[0131] Comparative Example 2 Preparation of Co 3 O 4 The difference between IrCoMnO / CC prepared in Example 1 and IrCoMnO / CC is that it is not doped with Mn and precious metal Ir, and can be used as a basic control group.

[0132] The difference between the IrCoO / CC prepared in Comparative Example 3 and the IrCoMnO / CC prepared in Example 1 is that no metal Mn is doped, which can be used to determine the effect of metal Mn on the catalyst structure.

[0133] The difference between the preparation of CoMnO / CC in Comparative Example 4 and the preparation of IrCoMnO / CC in Example 1 is that the precious metal Ir is not added, and the comparative example 4 can be used as an active control group.

[0134] Comparative Example 2 (Co 3 O 4 / CC), comparative example 3 (IrCoO / CC), comparative example 4 (CoMnO / CC) and example 1 (IrCoMnO / CC) were structurally characterized. The results are as follows Figure 2 As shown in Figure 4, the lattice expansion caused by the substitution of Co by Mn ions with larger ionic radius indicates successful Mn doping. Due to the small size of the nanoparticles formed by Ir, no diffraction peaks related to Ir species were observed in IrCoMnO / CC and IrCoO / CC.

[0135] Comparative Example 2 (Co 3 O 4 / CC), Comparative Example 3 (IrCoO / CC), Comparative Example 4 (CoMnO / CC) and Example 1 (IrCoMnO / CC) Raman spectroscopy test ( Figure 3 ) and SEM test results ( Figure 4 ) are basically the same, showing an ordered sheet-like nanoarray morphology with a cross-linked structure. Using high-resolution transmission electron microscopy ( Figure 5 ) observed the morphology and corresponding element distribution of Example 1 (IrCoMnO / CC) again, proving that Mn and Ir were successfully introduced into the catalyst. 2 ) nanoparticles, thereby accurately drawing relevant conclusions and determining the exact structure of the final sample IrCoMnO / CC.

[0136] The three-electrode system was used to study the oxygen evolution activity of each catalyst in the electrolysis of water in an acidic medium. The experiment was carried out in a sulfuric acid medium, with graphite as the counter electrode and mercury / mercurous sulfate electrode as the reference electrode. Linear sweep voltammetry test results ( Figure 6 ) shows: At a current density of 10 mA cm -2 When the overpotential of Example 1 (IrCoMnO / CC) is only 269 mV, it is much better than that of Comparative Example 2 (Co 3 O 4 / CC (η=521mV), Comparative Example 3—IrCoO / CC (η=320mV) and Comparative Example 4—CoMnO / CC (η=320mV). The linear sweep voltammetry curves of each sample were processed according to the Tafel equation to obtain the corresponding Tafel curves, and linear fitting was performed to explore the oxygen evolution reaction kinetics of the prepared catalysts ( Figure 7 ). Example 1 - The Tafel slope of IrCoMnO / CC is 70.1 mV·dec -1 , significantly lower than that of Comparative Example 2—Co 3 O 4 / CC(113.5mV·dec -1 ), Comparative Example 3—IrCoO / CC (72.0 mV·dec -1 ) and Comparative Example 4—CoMnO / CC (109.1mV·dec -1 ), the charge transfer coefficient of IrCoMnO / CC is higher, and the IrO 2 The addition of Mn can effectively promote rapid charge transfer and material diffusion, thus making the sample have faster oxygen evolution reaction kinetics. The specific results are shown in Table 1.

[0137] Table 1 Electrochemical performance test results of various embodiments and comparative examples

[0138]

[0139] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the implementation steps or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0140] The present invention is not limited to the structures which have been described above and shown in the drawings, and various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.

Claims

1. A cobalt-based oxide catalyst material, characterized in that: The following raw materials are included in mass percentage: Carbon cloth 0.66-4.66%; Cobalt salt 24.82-34.82%; Methylimidazole 62.32-73.32%; Manganate 0.01-0.1%; Iridium salt 0.01-0.1%.

2. The method for preparing a cobalt-based oxide catalyst material according to claim 1, characterized in that: The cobalt salt is cobalt nitrate hexahydrate, and the methylimidazole is 2-methylimidazole.

3. The method for preparing a cobalt-based oxide catalyst material according to claim 1, characterized in that: The manganate is potassium permanganate, and the iridium salt is iridium trichloride hydrate.

4. A method for preparing a cobalt-based oxide catalyst material, characterized in that: include: Cutting the carbon cloth into a preset size, performing surface treatment on the carbon cloth by ultrasonic cleaning, and soaking the surface treated carbon cloth in deionized water; Weighing a cobalt salt and methylimidazole to prepare a mixed solution, immersing the carbon cloth in the mixed solution, and performing a reaction, washing, and drying process to obtain dimethylimidazole cobalt supported on the carbon cloth; The carbon cloth-supported dimethylimidazole cobalt is immersed in a manganate solution to obtain manganese-doped dimethylimidazole cobalt supported on the carbon cloth, and the washed and dried manganese-doped dimethylimidazole cobalt supported on the carbon cloth is immersed in an iridium salt solution to obtain manganese-iridium-doped dimethylimidazole cobalt supported on the carbon cloth; The manganese iridium doped dimethyl imidazole cobalt supported on carbon cloth is placed in an air atmosphere environment and heated to prepare a carbon cloth supported cobalt-based oxide catalyst material.

5. The method for preparing a cobalt-based oxide catalyst material according to claim 4, characterized in that: The surface treatment of the carbon cloth by ultrasonic cleaning comprises: Soak the carbon cloth in an acetone cleaning tank and ultrasonically clean it for 30 minutes; Soak the carbon cloth in an ethanol cleaning tank and ultrasonically clean it for 30 minutes; Soak the carbon cloth in a clean water tank and wash for 30 minutes; Soak the carbon cloth in a concentrated nitric acid cleaning tank and ultrasonically clean it for 4 hours; Soak the carbon cloth in a clean water tank and wash it until the pH value on the surface of the carbon cloth is neutral.

6. The method for preparing a cobalt-based oxide catalyst material according to claim 4, characterized in that: The method of weighing a cobalt salt and methylimidazole to prepare a mixed solution, immersing the carbon cloth in the mixed solution, and performing a reaction, washing, and drying process to obtain dimethylimidazole cobalt supported on the carbon cloth comprises: Weigh cobalt salt and dissolve it in deionized water, stir evenly to obtain cobalt nitrate solution; Weigh methylimidazole and dissolve it in deionized water, stir evenly to obtain a methylimidazole solution; adding the methylimidazole solution to the cobalt nitrate solution to obtain a mixed solution; The carbon cloth was immersed in the mixed solution, reacted at room temperature for 4 hours, repeatedly washed with deionized water, and dried in an oven to obtain dimethylimidazole cobalt supported on the carbon cloth.

7. The method for preparing a cobalt-based oxide catalyst material according to claim 6, characterized in that: The cobalt salt is cobalt nitrate hexahydrate, and the methylimidazole is 2-methylimidazole.

8. The method for preparing a cobalt-based oxide catalyst material according to claim 6, characterized in that: The temperature of the oven is 60°C.

9. The method for preparing a cobalt-based oxide catalyst material according to claim 4, characterized in that: The method of immersing the carbon cloth-supported dimethyl imidazole cobalt in a manganate solution to obtain the carbon cloth-supported manganese-doped dimethyl imidazole cobalt, and immersing the washed and dried carbon cloth-supported manganese-doped dimethyl imidazole cobalt in an iridium salt solution to obtain the carbon cloth-supported manganese-iridium-doped dimethyl imidazole cobalt comprises: Weigh permanganate and dissolve it in deionized water, stir evenly to obtain a manganate solution; The carbon cloth-supported dimethyl imidazolium cobalt is immersed in a manganate solution, and then ice-bathed, washed and dried to obtain the carbon cloth-supported manganese-doped dimethyl imidazolium cobalt; Weigh iridium salt and dissolve it in deionized water, stir evenly to obtain an iridium salt solution; The manganese-doped dimethylimidazole cobalt supported on the carbon cloth is immersed in an iridium salt solution, and the manganese-iridium-doped dimethylimidazole cobalt supported on the carbon cloth is obtained through immersion, washing and drying.

10. The method for preparing a cobalt-based oxide catalyst material according to claim 9, characterized in that: The step of immersing the carbon cloth-supported cobalt dimethyl imidazole in a manganate solution, performing an ice bath, washing, and drying to obtain the manganese-doped cobalt dimethyl imidazole supported on the carbon cloth comprises: The dimethylimidazole cobalt supported on the carbon cloth was placed in an ice bath in a potassium permanganate solution for 30 minutes, and the dimethylimidazole cobalt supported on the carbon cloth was taken out and repeatedly washed with deionized water and ethanol; The washed carbon cloth-supported dimethyl imidazole cobalt is placed in a vacuum drying oven, and after vacuum drying, manganese-doped dimethyl imidazole cobalt supported on the carbon cloth is obtained.

11. The method for preparing a cobalt-based oxide catalyst material according to claim 10, characterized in that: The temperature of the vacuum drying oven is 100°C.

12. The method for preparing a cobalt-based oxide catalyst material according to claim 11, characterized in that: The step of immersing the carbon cloth-supported manganese-doped cobalt dimethyl imidazole into an iridium salt solution, and obtaining the carbon cloth-supported manganese-iridium-doped cobalt dimethyl imidazole by immersing, washing and drying comprises: The manganese-doped dimethyl imidazolium cobalt supported on the carbon cloth was immersed in an iridium trichloride hydrate solution for 24 hours, and the manganese-doped dimethyl imidazolium cobalt supported on the carbon cloth was taken out and rinsed with deionized water; The washed carbon cloth-loaded manganese-doped dimethyl imidazole cobalt is placed in a constant temperature box and dried at a constant temperature to obtain the carbon cloth-loaded manganese-iridium-doped dimethyl imidazole cobalt.

13. The method for preparing a cobalt-based oxide catalyst material according to claim 12, characterized in that: The temperature of the thermostat is 60°C.

14. The method for preparing a cobalt-based oxide catalyst material according to claim 4, characterized in that: The method of placing the carbon cloth-supported manganese iridium-doped dimethyl imidazole cobalt in an air atmosphere and heating the carbon cloth-supported cobalt-based oxide catalyst material comprises: The carbon cloth-supported manganese iridium-doped dimethyl imidazole cobalt was heated to 300° C. at a heating rate of 2° C. / min in an air atmosphere and kept heated for 4 hours to obtain a carbon cloth-supported cobalt-based oxide catalyst material.

15. The method for preparing a cobalt-based oxide catalyst material according to claim 14, characterized in that: The manganate is potassium permanganate, and the iridium salt is iridium trichloride hydrate.

16. An application of a cobalt-based oxide catalyst material, characterized in that: The cobalt-based oxide catalyst material according to any one of claims 1 to 3 is used for electrolysis of water.

Citation Information

Patent Citations

  • High-orientation manganese-cobalt oxide dodecahedron material and preparation method thereof

    CN111362315A

  • Preparation method of MOF derived hollow cobalt oxide loaded manganese oxide catalyst as well as product and application thereof

    CN112569961A

  • Acidic oxygen evolution electrocatalyst and preparation method thereof

    CN117026293A